Southern right whale (Eubalaena australis), seasonal abundance and distribution at Head of Bight, South Australia - Charlton, Claire; Ward, Rhianne; McCauley, Robert; Brownell, R.L.; Salgado Kent, Chandra; Burnell, S. (WILEY, 2019)
© 2019 John Wiley & Sons, Ltd.